An Analysis of the Conceptual and Functional Factors Affecting the Effectiveness of Proton-Exchange Membrane Water Electrolysis - Gaydaa AlZohbi (ChemEngineering)
Hydrogen has the potential to decarbonize the energy and industrial sectors in the future, mainly if it is generated by water electrolysis. The proton-exchange membrane water electrolysis (PEMWE) system is regarded as a propitious technology to produce green hydrogen from water using power supplied by renewable energy sources. It offers many benefits, such as high performance, high proton conductibility, quick response, compact size, and low working temperature. Many conceptual and functional parameters influence the effectiveness of PEM, including temperature, pressure of anode and cathode regions, water content and wideness of the layer, and cathode and anode exchange current density. In addition, the anodic half-reaction (known as the oxygen evolution reaction (OER)) and cathodic half-reaction (known as the hydrogen evolution reaction (HER)) perform an important function in the development of PEMWE. The current study aims to present these parameters and discuss their impacts on the performance of PEM. Also, the PEM efficiency is presented. The different methods used to enhance the scattering of OER electrocatalysts and minimize catalyst loading to minimize the price of PEMWE are also highlighted. Moreover, the alternative noble metals that could be used as electrocatalysts in HER and OER to minimize the cost of PEM are reviewed and presented.